2018
DOI: 10.1556/2006.7.2018.07
|View full text |Cite
|
Sign up to set email alerts
|

Eveningness is associated with poor sleep quality and negative affect in obsessive–compulsive disorder

Abstract: BackgroundObsessive–compulsive disorder (OCD) is characterized by intrusive thoughts and repetitive behaviors that severely encumber daily functioning. OCD patients seem to exhibit sleep disturbances, especially delayed bedtimes that reflect disrupted circadian rhythmicity. Morningness–eveningness is a fundamental factor reflecting individual variations in diurnal preferences related to sleep and waking activities. Eveningness reflecting a delayed sleep–wake timing has repeatedly been associated with sleep pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Participants were asked to rate the extent to which they experienced each emotion in general (1 = very slightly or not at all; 5 = very much). Previous studies (e.g., Gyollai et al 2011;Simor et al 2018) tended to support its reliability and factorial structure.…”
Section: Methodsmentioning
confidence: 92%
“…Participants were asked to rate the extent to which they experienced each emotion in general (1 = very slightly or not at all; 5 = very much). Previous studies (e.g., Gyollai et al 2011;Simor et al 2018) tended to support its reliability and factorial structure.…”
Section: Methodsmentioning
confidence: 92%
“…They found that eveningness can be a predictor of sleep quality. [ 9 ] The reason for this difference in the results could go back to the different tools used for examining the ME chronotypes. Therefore, further studies with different tools are needed to determine the wider dimensions of the effects of ME chronotypes on sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor related to the sleep quality is Morning-Evening (ME) chronotypes. [ 9 ] Individuals differ in diurnal preferences, sleep-wake patterns, and alertness in the morning and evening. Morning-types get out of bed early and are usually more alert in the first half of the day and go to bed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Diurnal affect variations have been reported in healthy and depressed populations but had a smaller amplitude in the latter [32]. Interestingly, while several studies have shown that eveningness is associated with greater depression and lower PA [14], the evidence supporting the association between eveningness and NA is scarce and mostly observed in clinical populations only [33].…”
Section: Self-report Studiesmentioning
confidence: 99%
“…Open Sci. 8: 201900 Interestingly, while several studies have shown that eveningness is associated with greater depression and lower PA [14], the evidence supporting the association between eveningness and NA is scarce and mostly observed in clinical populations only [33].…”
Section: Self-report Studiesmentioning
confidence: 99%